Perspectives on supplier innovation : Theories, concepts and empirical insights on open innovation and the integration of suppliers - Brem, Alexander; Tidd, Joe (London Imperial College Press, 2012)
This volume provides a comprehensive overview of theories, concepts and empirical insights on supplier innovation within the framework of open innovation and integration of suppliers into value-creation processes.
Keywords: Quản trị kinh doanh